2014
DOI: 10.1007/s00540-014-1940-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nicardipine or esmolol on the onset time of rocuronium and intubation conditions during rapid sequence induction: a randomized double-blind trial

Abstract: Pretreatment with nicardipine for RSI improved intubation conditions and shortened the onset time of rocuronium and attenuated changes in MAP after intubation. Esmolol may disturb intubation conditions and the onset of action of rocuronium, despite being effective in alleviating responses of HR after RSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Esmolol: This selective beta blocker has negative inotropic and chronotropic effects. Combining this drug with NMBDs may delay the onset of action [ 35 ].…”
Section: Factors That Affect Onset Timementioning
confidence: 99%
“…Esmolol: This selective beta blocker has negative inotropic and chronotropic effects. Combining this drug with NMBDs may delay the onset of action [ 35 ].…”
Section: Factors That Affect Onset Timementioning
confidence: 99%
“…This is not desirable in a rapid sequence intubation scenario where we want good relaxation and that too quickly. Lee et al [19] have shown that nicardipine hastens the onset of action as compared to esmolol.…”
Section: Discussionmentioning
confidence: 99%
“…Efe ve arkadaşlarının 19 yapmış olduğu çalışmada ise esmolol infüzyonu bolus esmolol uygulaması ile karşılaştırılmış ve infüzyon olarak uygulanan esmololun entübasyon ve sternotomi sırasında sistolik arteriyel kan basıncını kontrol etmekte daha etkin olduğu gösterilmiştir. Bunun yanı sıra esmololün hızlı seri entübasyondan sonra kalp hızı yanıtını baskılamasına rağmen roküronyumun etki başlangıcını bozabileceği ve dolayısıyla entübasyonu olumsuz etkileyebileceği de belirtilmiştir 20 .…”
Section: Bulgularunclassified